Examination of self patterns: framing an alternative phenomenological interview for use in mental health research and clinical practice - Daly, Anya; Ritunnano, Rosa; Gallagher, Shaun; Kirmayer, Laurence J.; Van Dam, Nicholas; Kleinman, Joshua (Frontiers in Psychology, 2024)
Mental disorders are increasingly understood as involving complex alterations of self that emerge from dynamical interactions of constituent elements, including cognitive, bodily, affective, social, narrative, cultural and normative aspects and processes. An account of self that supports this view is the pattern theory of self (PTS). The PTS is a non-reductive account of the self, consistent with both embodied-enactive cognition and phenomenological psychopathology; it foregrounds the multi-dimensionality of subjects, stressing situated embodiment and intersubjective processes in the formation of the self-pattern. Indications in the literature already demonstrate the viability of the PTS for formulating an alternative methodology to better understand the lived experience of those suffering mental disorders and to guide mental health research more generally. This article develops a flexible methodological framework that front-loads the self-pattern into a minimally structured phenomenological interview. We call this framework ‘Examination of Self Patterns’ (ESP). The ESP is unconstrained by internalist or externalist assumptions about mind and is flexibly guided by person-specific interpretations rather than pre-determined diagnostic categories. We suggest this approach is advantageous for tackling the inherent complexity of mental health, the clinical protocols and the requirements of research.